Birth Order and its Relationship to the Lifestyles of Adolescent Students: رحاب عارف السعدي (Journal of the College of Education for Women, 2021)
This study aims to know the relationship between the birth order and lifestyles among a sample of adolescent students. The sample of the study consisted of (200) students selected from the governmental schools in the Directorate of Education of Qabatiya, in the second semester of the academic year 2020/2021. The results of the study have revealed that the most common lifestyles among the sample of the study are represented by: (the belonging) style, (the submissive) style, (the avenger) style, (the pampered) style, respectively. The study has also found that there are statistically significant differences in the lifestyles of: (the victim, the domineering, the avenger, and the harmful) which are ascribed to the gender variable. Moreover, there are statistically significant differences in (the pampered) style in favour of the female students. The study has also indicated that there is no statistically significant relationship between the birth order and the lifestyles among the sample of the study. The researcher has recommended conducting more studies which deal with birth order and the lifestyles with other variables and other categories.